Fetish : an erotics of culture - Krips, Henry (Cornell University Press, 1999)
In Fetish, Henry Krips draws together Freudian and Marxian insights to provide accounts of fetishism and the gaze that afford new ways of understanding the relation of the individual to the social, of pleasure to desire. He uses discrete cultural artifacts as windows through which to view local instances of the mediation of pleasure and desire, demonstrating that users of cultural objects adapt them to suit their own strategic ends. Ranging widely over texts and cultures, he discusses Hopi initiation rites, Holbein's painting The Ambassadors, Robert Boyle's early scientific manual New Experiments Physico-Chemical, Toni Morrison's Beloved, the popular television series Mystery Science Theatre 3000, and David Cronenberg's film Crash. Jacques Lacan's theory of the gaze and Louis Althusser's theory of ideology frame Krips's perspectives on fetishism and the discourse of perversion, which he considers in light of postcolonial theory, the history of science, screen theory, and, of course, psychoanalysis. What results is a work remarkable for its clear exposition and its sophisticated synthesis of major theorists, its provocative argument that pleasure comes not from attaining desire but rather from moving around its object-cause.